VALIDITY OF APPLICANTS PRESENT BEFORE A NOTARY ONLINE - Arbas, Etra (NOMOI Law Review, 2025)
The development of digital technology has brought significant changes in various fields, including in notarial practice. One of the main challenges in implementing online notarization is the validity of the person appearing before the notary online (online notarization). Clear regulations are needed to ensure that the online notarization process remains in accordance with the principles of legality, identity authentication, and personal data protection. In addition, the legal validity aspect of deeds made online is also a major concern in the applicable legal system. This study uses normative legal research with a statutory and comparative approach. The results of the study show that online notarization has been in effect and implemented in several countries. Indonesia itself has not implemented online notarization because existing regulations require that the person appearing must be present in person before the notary. So if the notary does not meet in person, then the validity of a deed is because it is carried out in a manner that is not in accordance with statutory regulations.